Critical thinking skills for your social work degree - Bottomley, Jane (Senior language tutor); Cartney, Pat; Pryjmachuk, Steven, 1964- (Critical study skills for education students., 2019)
An essential text for all those undertaking a social work degree within higher education, providing study support and skills development for critical thinking, reading and writing.